Estimación preliminar del impacto económico en los usuarios finales durante la implementación de la televisión digital terrestre en Colombia (2007)
ABSTRACT: The objective of the study is to evaluate the impact that will have the introduction of the digital television (TVD) in Colombia. It is possible to indicate that the estimation of the economic impact of the migration towards a system of TVD on the different involved actors, will depend on different factors, between which they are you rule regulatory and of public policies that the government adopts. Other determinants of the transition process will be the technological and commercial evolution of the production equipment, transmission and audio-visual reception; the strategies that the operators of the telecommunications in Colombia adopt The previous factors, as well as the high degree of uncertainty with respect to the acceptance on the part of the Colombian users of the new services, and on the integration of already existing services, constitute a limitation for the reaches of this study.